The effectiveness of visual media in literature-based classroom / Nor Azyyati Md Saad - Md Saad, Nor Azyyati (2009)
This research is carried out as a survey on Part Five and Part Eight TESL students of Faculty of Education, UiTM perceptions towards the effectiveness of visual media in Literature classroom. The purpose of this research is to fin d out the effectiveness of implementing visual media in the teaching of Literature towards students ’ interest and understanding of Literature texts. A survey has been conducted and data was collected via questionnaire and interview. The questionnaire was distributed to the students to gain information needed for this research. Based on the findings, the research revealed that a majority of the students or respondents stated that they liked and enjoyed with the visual media been implemented in their Literature classroom. Furthermore, these students had the perception that visual media did help to boost up their interest towards Literature and enhance their understanding of Literature texts. Data from the interview added that majority of the Part Eight respondents had used visual media in teaching Literature during their teaching practicum. Many insights and suggestion relating to the issue has been raised by the respondents.